2012
DOI: 10.2134/agronj2011.0342
|View full text |Cite
|
Sign up to set email alerts
|

Spring Wheat Yield and Quality Related to Soil Texture and Nitrogen Fertilization

Abstract: Efficient N fertilization is crucial for economic wheat (Triticum aestivum L.) production and is of great agronomical and environmental significance. A study was conducted at 12 site‐years in eastern Canada to evaluate the effect of soil surface textural groups, N rate (0–200 kg N ha−1) and application timing on grain yield (GY), N uptake, nitrogen uptake efficiency (NUE), grain protein content (GPC), test weight, and thousand kernel weight (TKW). Chlorophyll meter readings (CMR) were taken at tillering and at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
24
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 54 publications
6
24
1
1
Order By: Relevance
“…However, the reason for this was unclear. Using similar sites to our study and the same textural groups, Nyiraneza et al (2012a) also found no effect of soil textural group on wheat grain yield. There were also significant linear and quadratic effects of N rate, as well as significant linear and quadratic N rate interactions with soil texture on grain yield (Table 3).…”
Section: Corn Yield Tnu and Nuesupporting
confidence: 78%
See 2 more Smart Citations
“…However, the reason for this was unclear. Using similar sites to our study and the same textural groups, Nyiraneza et al (2012a) also found no effect of soil textural group on wheat grain yield. There were also significant linear and quadratic effects of N rate, as well as significant linear and quadratic N rate interactions with soil texture on grain yield (Table 3).…”
Section: Corn Yield Tnu and Nuesupporting
confidence: 78%
“…Potato was the only previously grown crop for the Sp soil textural group, whereas corn, soybean, and wheat were previously grown at the other textural groups, depending on year and specific location (Table 1). A previous study with wheat on similar sites also reported comparable findings on preplant soil mineral N concentration (Nyiraneza et al 2012a).…”
Section: Soil Mineral N Concentrationsupporting
confidence: 70%
See 1 more Smart Citation
“…Our results showed that there was a greater increase in yield under conditions of coarse soil texture versus fine and medium soil textures ( Figure 7A). A study also showed that N fertilization and soil textural group effects were significant on all measured parameters and their interaction was significant on grain protein content, thousand-kernel weight, test weight, and chlorophyll meter readings [24]. Soil N also influenced effects of N fertilizer on crop yield, and the lnR was found to decrease with the increase soil total N and available N ( Figure 15A,B).…”
Section: Soil Factorsmentioning
confidence: 85%
“…Wheat N fertilizer is influenced by weather such as the temperature as well as the amount and frequency of rainfall during the growing season [24]. Wheat is one of the most sensitive crops to high temperature [25].…”
Section: Climatementioning
confidence: 99%